Adaptation of the Participant Role Scale (PRS) in a Spanish Youth Sample: Measurement Invariance Across Gender and Relationship With Sociometric Status. (November 2014) - Lucas-Molina, Beatriz; Williamson, Ariel A.; Pulido, Rosa; Calderón, Sonsoles
In recent years, bullying research has transitioned from investigating the characteristics of the bully–victim dyad to examining bullying as a group-level process, in which the majority of children play some kind of role. This study used a shortened adaptation of the Participant Role Scale (PRS) to identify these roles in a representative sample of 2, 050 Spanish children aged 8 to 13 years. Confirmatory factor analysis revealed three different roles, indicating that the adapted scale remains a reliable way to distinguish the Bully, Defender, and Outsider roles. In addition, measurement invariance of the adapted scale was examined to analyze possible gender differences among the roles. Peer status was assessed separately by gender through two sociometric procedures: the nominations-based method and the ratings-based method. Across genders, children in the Bully role were more often rated as rejected, whereas Defenders were more popular. Results suggest that although the PRS can reveal several different peer roles in the bullying process, a more clear distinction between bullying roles (i.e., Bully, Assistant, and Reinforcer) could better inform strategies for bullying interventions.